Review of research on kokum, camboge and related species - Mathew, Y S Rao, Gilu Lizy George, R Lakshmanan, K Mary (Journal of Spices and Aromatic Crops, 2002)
Garcinia species are distributed throughout the tropics and have tremendous potential, both as spices and medicinal plants. Though there are more than 200 species in the genus, only 20 are found in India. The two species namely Garcinia gummi-gutta (L) Rob. (camboge) and G. indica Choisy (kokum) are widely distributed in the Western Ghats and are very popular in Sooth Indian cuisine. Recently excited the scientific world for processing properties that regulate obesity. Though commercially important, these species remained neglected and not much attention was given for their research and development. In this review, an attempt has been made to collect and compile the available information so that areas of interest could easilly be identified for further investigation and research.